IFPRI 2010 Annual Report - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
In 2010, the international development community focused on a range of complex issues—childhood malnutrition, natural disasters, volatile food prices, climate change, global trade—that require both immediate and long-term attention. As these subjects have direct implications for poverty and hunger, IFPRI sought ways to address them through evidence-based research, outreach, and concrete policy recommendations. For example, recent findings showing that the window of opportunity for improving children's nutrition spans the 1,000-day period between conception and a child's second birthday led IFPRI to recommend that governments invest in nutrition interventions targeting mothers and infants. IFPRI's research in Pakistan after the devastating 2010 floods led to policy-relevant observations on post-disaster recovery, including the need to strengthen institutions in developing countries so they are better prepared to coordinate large-scale disaster responses. On the topic of volatile food prices, IFPRI recommended that, among other approaches, governments reform biofuel policies, especially in the United States and Europe, to reduce biofuels' effects on food markets.